Perancangan dan Pembuatan Aplikasi Pendeteksi Kesalahan Penempelan Barcode pada Kemasan Produk Menggunakan Sistem Arduino Uno dan Sistem Komputasi (Studi Kasus PT. Duta Nichirindo Pratama) - Ade Sumaedi; Makhsun Makhsun; Achmad Hindasyah (Jurnal Informatika Universitas Pamulang, 2020)
PT. Duta Nichirindo Pratama is a company engaged in the field of Autoparts Manufacture. Barcode is the identity of an item / product on the package. Barcode technology has been used as the identity of goods in a production. Barcodes are used to facilitate the identification of goods produced. Paste the barcode on the packaging of packaging results at PT. Duta Nichirindo Pratama is done manually, but there are often errors attached to the barcode on a similar packaging. This research will design and create a system based on Visual Basic.Net and Arduino to select barcode attachment errors that have the potential to be sent to consumers. The system is designed using Unified Modeling Language (UML) diagrams, database design and interface menu design. The system created will then be tested to detect the black box test. With a computing-based design system that functions to detect barcodes on the packaging automatically, the problem of sticking barcodes on the packaging can be detected.